#TITLE_ALTERNATIVE# - NURDIN (NIM :25114007); Pembimbing : Prof. Dr. Ir. Hasanuddin Z. A., M.Sc.; Dr. Ir. Eka Djunar, AMIN
Land boundary problem between Indonesia and Malaysia is due to, among other things, the unclarity of international boundary between the two countries. One of the locations where boundary is an issue is the area of west coast of Sebatik Island, Terusan Tamboe and Terusan Sikapal. Referring to the principle of “uti posidetis juris”, the boundary in said area is mentioned in the 1915 Agreement between The Neitherland and The British wich declare where it starts from the west pillar of Sebatik Island thence keeping middle of channel and connected finally to watersheed of Bukit Sikapal by a line taken perpendicular. Unfortunately the 1915 Agreement does not specify any geodetic datum and the method used to determine the middle of the channel. Therefore, it is necessary to figure out some options of delimitation by applying equidistance method as stated in UNCLOS (United Nations Convention on The Law of The Sea) and IHO (International Hydographic Organization) and the Three Stage Approach method practiced by ICJ (International Court of Justice) and ITLOS (International Tribunal for The Law of The Sea) in maritime boundary in order to define the middle of channel. The first step of the Three Stage Approach method is to construct equidistance line on some charts and satellite images. The second step is to determine the relevant circumtances in relevant area. The third step is to accomplish, the disproportionality test- to compare the lenght of coastline with the delimitation area. Finally, the median line of those methods are then compared in order to find the difference in the constructed the boundary line. Analisys are conducted base on the 1915 Agreement. Equidistance method and Three Stage Approach method can be applied in said water area delimitation as part of land boundary. There are some options of west pilar of Sebatik Island’s latitude lines and three options of perpendicular lines. Sedam Island situated in Malaysia region is a relevant circumstances that affects the position of centre point of west coast of Sebatik Island. The disproportionality test comparing the lenght of coastline to the delimitation area between Indonesia and Malaysia indicates a proportional comparison in both options which are 1) giving full effect to Sedam Island and 2) giving nil effect to Sedam Island.